A gender perspective on social media tagging: The case of Twitter hashtags of Gezi Park protests - Jale Balaban-Salı; Şeyma Esin Erben (Cultura, Lenguaje y Representación, 2016)
Gezi Park Protests are undoubtedly one of those recent mass protests occupying an important place in the global agenda. The protests were initially to oppose the construction of the 19th century Ottoman Artillery Barrack within the area of Gezi Park without reconstruction permit. Upon police’s severe intervention to the tens of people keeping cave in the park to save the trees to be cut, the number of those who interacted with each other in social media increased rapidly, turning Gezi Park into a place for contrarian forces to unite. During the protests, all kinds of support, help and cooperation calls are made through social media. The solidarity in Gezi Park became apparent in social media content, showing a general attitude against every kind of discrimination. In this study, we argue whether the  sexist discourse used by the protesters related to Gezi Park Protests has been reconstituted by the Twitter hashtags. The Twitter hashtags such as #kirmizilikadin (lady in red), #gazdanadam (gasman), #direnayol (resist ayol), #duranadam (standing man) have been studied, in the context of gender, by the technique of discourse analysis, which is one of the qualitative research methods. People use social tagging with their own words in the way how they conceive the state. The study concludes that the Twitter hashtags on Gezi Park Protests emphasize the power and sovereignty of men while focusing on the appearance and